Mathematical simulation of heat transfer and chemical reaction in a swirling flow of equilibrium-dissociating gas - Matvienko, Oleg V. (Journal of engineering physics and thermophysics)
Results of investigations of the heat transfer in the swirling turbulent flow of dinitrogen tetroxide in a cylindrical channel are presented. The equilibrium stage of the dissociation reaction N2O4 (sic) 2NO(2) was considered. It was established that the mass fraction of N2O4 in its swirling flow is smaller than that in the analogous forward flow at one and the same distance from the input cross section of the channel. In the case where the flow of dinitrogen tetroxide is strongly swirled, its intense heating in the zone of reverse flows near the channel inlet causes it to dissociate. It is shown that an increase in the swirling of a gas flow intensifies the heat transfer in it with increase in its Nusselt number.